RESEARCH ALGORITHM AND CIRCUIT OF NUMERICAL CONTROL SYSTEM IN THE OPTICAL GRINDING MACHINE CNC MB-250 - Hùng, Nguyễn Trọng; Đức, Vũ Duy; Hải, Phạm Quốc; Võ, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARYThis paper presents some research’s results on algorithms, programming, and communication of rotation speed controller system that is used in CNC grinding machine MB-250. Digital control system uses a method of controlling the negative voltage DC servo motors, the PID algorithm, microcontroller PIC 16F877A and PIC 18F4550. The spindle speed control program is transmitted from the computer through USB communication via the master and slave, with feed-back loop, improving the precision controls to achieve the technology’s requirements.With the success of research results, creating the ability to complete the design and manufacture of digital control systems as models of industrial use in order to integrate more CNC optical grinding machine.